Cotidiano, identidade e memória: narrativas de camelôs em Pelotas (RS) - Goularte, Cláudia Cardoso (2008)
This dissertation primary goal is to discuss the formality/informality phenomenon among the specificity occupation of the street vendors (Camelôs), in the so called Pelotas Camelódromo, an ethnography of such space is proposed in a correlation with the concepts of group identity and collective memory. From a methodological approach lined in the individual worker s stories we analyze the period between the years of 1997 to 2007. The issues surrounding how identities are built among workers and how that is revealed opposing and complementing the fact they consider and name themselves small businessmen and women, it is expressed in their testimonials and becomes the main issue in the research. These worker s life stories are filled of reasons for their place in the world, in that function and not another, and for reasons not to predict a future in such unstable livelihood, where the risks originated from smuggling merchandise, forging products and tax evasion, materialize in the countless stories of loss of merchandise resold, leading to money loss, debts and, often, to the impossibility to work and keep an occupation, that in spite of crimes and infractions from a legal point of view, it is considered by those interviewed as dignify work. During four years I ve establish connections and went regularly to Pelotas Camelódromo, what made possible obtaining depositions over the main issues that are part of their everyday at work and relate directly to building their identities and memories.